Controlling Geometry and Flow Through Bacterial Bridges on Patterned Lubricant‐Infused Surfaces (pLIS). Issue 52 (20th November 2020) - Lei, Wenxi; Krolla, Peter; Schwartz, Thomas; Levkin, Pavel A.
Abstract: Spatial control of bacteria and biofilms on surfaces is necessary to understand the biofilm formation and the social interactions between bacterial communities, which could provide useful hints to study the biofilm‐involved diseases. Here patterned lubricant‐infused surfaces (pLIS) are utilized to fabricate connective structures named "bacterial bridges" between bacterial colonies of Pseudomonas aeruginosa by a simple dewetting method. It is demonstrated that the bacteria attached to hydrophilic areas and bacteria precipitated on lubricant infused borders both contribute to the formation of bacterial bridges. The geometry and distribution of bridges can be controlled using predesigned superhydrophobic–hydrophilic patterns. It is demonstrated that bacterial bridges connecting bacteria colonies act as bio‐microfluidic channels and can transport liquids, nutrients, and antibacterial substances between neighboring bacteria clusters. Thus, bacterial bridges can be used to study formation, spreading, and development of bacterial colonies, and communication within and between isolated biofilms. Abstract : Here, patterned lubricant infused surfaces (pLIS) are utilized to fabricate connective structure named "bacterial bridges" between bacterial colonies of Pseudomonas aeruginosa by a simple dewetting method. Geometry and distribution of bridges can be controlled. The bacterial bridges have good connectivity to act as bio‐microfluidic channels to transfer liquids, nutrients, or antibacterial substances between neighboring bacteria clusters.